A two-dimensional splashing model for investigating impingement characteristics of supercooled large droplets. (April 2016) - Wang, C.; Chang, S.; Leng, M.; Wu, H.; Yang, B.
Highlights: An SLD splashing model was developed. SLD collection efficiencies predicted by the splashing model were presented. SLD ice accretion affected by droplet splashing was performed. Good agreement between model predictions and experiments is observed. Droplet splashing and reimpingement during ice accretion was analyzed. Abstract: In this article, a two-dimensional (2D) splashing model is proposed to investigate the dynamics when supercooled large droplets (SLD) impinging on a wall surface in the aircraft-icing field. Energy conservation for droplet motion and impingement is used to capture the properties of the splashed droplets. A new statistical treatment of the droplet impinging energy and angle during the droplet-wall interaction is introduced in order to calculate the average dynamics of the SLD within a micro-control volume on wall surface. Based on the LEWICE predictions of droplet collection efficiencies and the available experimental ones, a new criterion for droplet splashing/deposition as well as a new formulation for the splashed mass is suggested. Lagrangian approach is adopted to describe the movement and impingement of SLD. The proposed model together with the previously developed droplet tracking method (DTM) for calculating droplet collection efficiency with the effect of droplet reimpingement constitute a relatively complete predicting approach of SLD impingement characteristics. Comparisons between the current predictions and the experimental observations, including SLD impingement over clean and contaminated airfoil surfaces as well as shapes of ice accretion in typical icing conditions, are carried out. Further, results obtained with the LEWICE splashing model are also plotted on the same graphs in order to assess the accuracy of the current splashing model in predicting SLD impingement. Results show that good agreement is achieved between the current predictions, including SLD impingement and ice accretion shapes, and the experimental ones. The predictions of the impingement distribution over contaminated surfaces obtained with the current splashing model show a much closer agreement with the experimental results than the ones obtained with LEWICE splashing model. For further investigation of SLD impingement, the properties of the droplet splashing and reimpingement during the ice accretion process are also addressed.